The hybridization of analytic hierarchy process and graph theory matrix approach (ahp-gtma) to solve solid waste transshipment site selection problem / Wan Nurdini Mior Abd Halim, Ilyana Farhin Mohd Hanafi, Nurul Izzati Johari, and Nor Faradilah Mahad - Mior Abd Halim, Wan Nurdini; Mohd Hanafi, Ilyana Farhin; Johari, Nurul Izzati; Mahad, Nor Faradilah (Universiti Teknologi MARA, 2022)
Proper selection of solid waste facilities is a complex issue and requires a broad assessment measure. Hence, the selection of these sites is a multiple criteria decision-making issue. This study proposed a hybridization of the Analytic Hierarchy Process and Graph Theory Matrix Approach (AHP-GTMA) method in selecting the best solid waste transshipment site. The objectives of this study are to apply the AHP-GTMA method to solve the solid waste transshipment site selection problem, and to determine the best solid waste transshipment site. Real-life empirical data about the solid waste transshipment site selection in Istanbul were used to demonstrate the application of the AHP-GTMA method. The data consisted of five alternatives of the solid waste transshipment site candidates in Istanbul labeled as A1, A2, A3, A4, and A5, and five criteria which were proximity to industrial solid waste (C1), proximity to household solid waste (C2), transportation simplicity (C3), necessity (C4) and proximity to residential area (C5). The findings revealed the ranking order of the criteria was C4 > C1 > C2 > C3 > C5 and the ranking order for the alternatives was given by A1 > A5 > A3 > A4 > A2. In conclusion, AHP-GTMA is successfully applied to solve the solid waste transshipment site selection problem.